„Okręt ludzi szczęśliwych...” – czyli o pielgrzymowaniu i migracji w relacji podróżnej Hanny Mortkowicz - Bernadeta Niesporek-Szamburska (Postscriptum Polonistyczne)
The paper presents Hanna Mortkowicz’s account of her trip to Palestine entitled W Palestynie. Obrazy i zagadnienia [In Palestine. Images and Issues] (1936) as a text read after many years, which can be inscribed, in dialogue with contemporary reportage (e.g. by Paweł Smoleński), in the intercultural dialogue currently in progress. The study shows how Mortkowicz opens the reader to the problem of migration. The writer does this by focusing her accounts on a group of Jews fleeing from Nazism – eternal wanderers, coming to Palestine in search of a new homeland. Text analysis shows how, thanks to Mortkowicz’s use of numerous narrative strategies and description techniques, such as: focalisation, personal narrative, and accumulation of space or time, she introduced her readers to the experience of newly-arrived refugees, people who are on the border between social existence and non-existence. In fact, a study of the text makes it possible to find that this forgotten title can provide reading matter to be used in the context of contemporary intercultural education.